A porous carbon supported metal monatomic-metal sub-nanocluster synergistic catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202610864915.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-06-16
AI Technical Summary
但在热解过程中,金属物种易发生迁移、聚集,导致纳米颗粒尺寸较大
本发明提供的多孔碳负载金属单原子-亚纳米簇协同催化剂,包括多孔碳载体,多孔碳载体上负载的原子邻近且存在电子相互作用的过渡金属单原子与亚纳米簇双活性位点。多孔碳载体提供快速传质通道并稳定锚定金属原子,金属亚纳米簇通过电子调控,增强了单原子位点的电子缓冲与电荷转移能力,提升了其在高电流下的活性和稳定性;同时,亚纳米簇与高度分散的过渡金属单原子共同大幅提高了活性位点密度与金属利用率。
Smart Images

Figure CN122382605B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic materials and energy catalysis technology, specifically relating to a porous carbon-supported metal single-atom-metal sub-nano cluster synergistic catalyst, its preparation method, and its application. Background Technology
[0002] Metal-organic frameworks (MOFs) are widely used in electrocatalytic material research due to their designable structures, high specific surface area, and uniform pores. Among them, ZIF-8, constructed from 2-methylimidazole and metal ions, possesses advantages such as stable coordination environment, good formability, and high nitrogen content in its derivatives, making it a commonly used precursor for constructing carbon-based electrocatalytic materials. ZIF-8 can be pyrolyzed to form a nitrogen-containing porous carbon framework, which can then be used to load metal active components. In existing technologies, metal active structures derived from ZIF-8 mainly fall into two categories: single-atom metal structures and metal nanoparticle structures.
[0003] The first category consists of single-atom catalysts derived from ZIF-8. Through confined coordination, individual metal atoms can be stably dispersed within a carbon support, forming well-defined coordination structures such as M–N4. These materials offer advantages such as high atom utilization and ample exposure of active sites. However, due to the lack of electronic synergy between metal atoms, their electron buffering capacity is limited; furthermore, under high current density or complex reaction environments, the charge transfer efficiency and structural stability of single-atom sites still struggle to meet the requirements for long-term operation.
[0004] The second type is metal nanoparticle catalysts formed by the pyrolysis of ZIF-8. These materials typically possess higher electronic conductivity and better interfacial charge transport capabilities, exhibiting good stability. However, during pyrolysis, metal species are prone to migration and aggregation, resulting in larger nanoparticle sizes. Consequently, their specific surface area decreases, metal utilization is insufficient, and some active sites struggle to effectively participate in the reaction.
[0005] In summary, existing ZIF-8 derived catalytic systems typically employ metal structure modulation at either the "single-atom" or "nanoparticle" scale, but both have limitations. Therefore, it is necessary to develop a novel metal structure modulation strategy that allows metal atoms to maintain a highly dispersed state while simultaneously forming moderately aggregated sub-nanoclusters. This would improve charge transfer efficiency, interfacial reaction kinetics, and durability, providing superior performance support for electrocatalytic reactions. Summary of the Invention
[0006] The purpose of this invention is to provide a porous carbon-supported metal single-atom-metal sub-nano cluster synergistic catalyst, its preparation method and application. By performing low-temperature preconditioning and high-temperature pyrolysis segmented sintering on the M-Zn / ZIF-8 precursor, an electrocatalytic hydrogen evolution catalyst with a transition metal single-atom-sub-nano cluster dual-active structure is constructed, which can significantly improve the intrinsic activity, conductivity and long-term stability of the catalyst in the electrocatalytic hydrogen evolution reaction.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a porous carbon-supported metal single-atom-metal sub-nanocluster synergistic catalyst, wherein the metal single-atom-metal sub-nanocluster synergistic catalyst comprises a porous carbon support, the surface of which is loaded with a dual-active-site structure of transition metal single atoms and sub-nanoclusters; the metal loading in the porous carbon-supported metal single-atom-metal sub-nanocluster synergistic catalyst is 0.5-5 wt%; the porous carbon support is an octahedral porous carbon prepared with a zinc-based zeolite imidazole framework as a precursor, and the transition metal is one of Fe, Co, Ni, Cu, and Pt; the transition metal single atoms and sub-nanoclusters are distributed in close proximity at the atomic scale, constituting a synergistic catalytic active center.
[0008] Secondly, the present invention provides a method for preparing the above-mentioned porous carbon-supported metal single-atom-sub-nanometer cluster catalyst, comprising the following steps: (1) Mix a methanol solution containing zinc nitrate hexahydrate with a methanol solution containing 2-methylimidazole until homogeneous to obtain solution A; (2) Dissolve the transition metal salt in methanol and stir until homogeneous to obtain solution B; (3) Add solution B to solution A and stir to react; centrifuge, wash and vacuum dry to obtain M-Zn / ZIF-8 precursor; (4) Under an inert atmosphere, the M-Zn / ZIF-8 precursor was subjected to segmented sintering, acid washing, centrifugation, washing and vacuum drying to obtain a porous carbon-supported metal single atom-metal sub-nano cluster synergistic catalyst. The segmented sintering refers to first heating the temperature to 150-250℃, preferably 180-210℃, at a heating rate of 2-5℃ / min, and holding it at that temperature for 40-120min; then heating the temperature to 600-1000℃, preferably 750-950℃, at a heating rate of 2-5℃ / min, and holding it at that temperature for 60-150min.
[0009] In step (1), the zinc salt and 2-methylimidazole solution are mixed preferentially, which allows zinc ions and organic ligands to pre-assemble, forming a well-structured and uniformly porous ZIF-8 octahedral framework, thus constructing a stable and rigid substrate with high specific surface area and abundant nitrogen coordination sites. Compared with the disordered preparation method of directly doping metals in the prior art, this operation can construct a stable confined structure in advance, providing sufficient attachment sites for the uniform anchoring of subsequent transition metals, inhibiting metal agglomeration from the source, and providing a structural prerequisite for the controllable coexistence of single atoms and sub-nano clusters of dual active sites.
[0010] In step (2), by dissolving the transition metal salt separately in methanol to prepare a homogeneous solution, the transition metal ions can be uniformly dispersed at the molecular level, effectively avoiding the problem of local metal concentration enrichment, and providing a stable and uniform metal precursor system for the subsequent controllable generation of single-atom and sub-nano cluster composite active structures.
[0011] In step (4), the low-temperature pre-calcination stage can solidify the ZIF-8 framework and promote the uniform anchoring of the metal precursor. Appropriately reducing the pre-calcination temperature or extending the holding time can increase the proportion of single atoms. The high-temperature pyrolysis stage realizes the carbonization of ligands and the volatilization of zinc to create pores. Increasing the pyrolysis temperature or extending the holding time can drive the metal atoms to migrate and aggregate appropriately, increase the content of sub-nano clusters, and effectively overcome the defects of uncontrollable structure and severe agglomeration in traditional processes.
[0012] Preferably, in step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 2~6:1.
[0013] Preferably, in step (2), the metal in the transition metal salt is any one of Fe, Co, Ni, Cu, and Pt.
[0014] Preferably, in step (3), the vacuum drying temperature is 60-100℃ and the vacuum drying time is 4-10h.
[0015] Preferably, in step (4), the metal loading in the porous carbon-supported metal single-atom-sub-nano cluster synergistic catalyst is 0.5-5 wt%, the acid washing solution is 0.01-0.1 M dilute hydrochloric acid, the acid washing time is 0.5-5 h, the vacuum drying temperature is 60-100 °C, and the vacuum drying time is 4-10 h.
[0016] Thirdly, the present invention provides an application of the porous carbon-supported metal single-atom-sub-nano cluster synergistic catalyst prepared by the above preparation method in the electrocatalytic hydrogen evolution reaction.
[0017] This invention provides a dual-site catalyst in which metal single atoms and sub-nano clusters coexist, and its preparation method. The method uses a metal-organic framework material as a precursor. First, a low-temperature pre-reconstruction treatment is performed under an inert atmosphere to induce migration and local aggregation of metal nodes. Then, high-temperature pyrolysis is carried out, causing some transition metal atoms to coordinate with the nitrogen-doped carbon matrix to form M–N. X Single-atom sites, along with locally enriched regions, are confined and transformed into metal sub-nanoclusters with sizes of 0.5–2 nm, thus constructing dual active sites. Finally, unstable species are removed by weak acid washing to optimize the exposure of active sites. This method ultimately achieves the synergistic construction of transition metal single atoms and sub-nanoclusters. Leveraging the excellent mass transfer properties of the porous carbon framework and the electronic complementarity between the metal single atoms and sub-nanoclusters, the electron transport efficiency and active site utilization of the catalyst are effectively improved, exhibiting excellent activity and stability in the electrocatalytic hydrogen evolution reaction.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The porous carbon-supported metal single-atom-subnanocluster synergistic catalyst provided by this invention comprises a porous carbon support, on which are supported dual active sites: transition metal single atoms with adjacent atoms and electronic interactions. The porous carbon support provides a rapid mass transfer channel and stably anchors the metal atoms. The metal subnanoclusters, through electronic modulation, enhance the electron buffering and charge transfer capabilities of the single-atom sites, thereby improving their activity and stability under high current. Simultaneously, the subnanoclusters and the highly dispersed transition metal single atoms together significantly increase the active site density and metal utilization.
[0019] This invention addresses the critical challenge of simultaneously achieving stable anchoring of transition metal atoms and controllable formation of sub-nanoclusters in the preparation of dual-active-site materials through staged sintering involving low-temperature pre-conditioning and high-temperature pyrolysis. In the low-temperature stage, strong chemical bonds are formed between the metal precursor and the carrier, ensuring stable anchoring of the metal species. In the high-temperature stage, thermally driven migration and bonding of weakly anchored neighboring atoms occur over extremely short distances, forming metal sub-nanoclusters, while the strongly anchored sites remain atomically dispersed. In contrast, traditional one-step pyrolysis methods involve simultaneous decomposition, reduction, and diffusion of the metal at high temperatures, easily leading to uncontrollable aggregation and the formation of large nanoparticles. This method constructs a coexistence structure of metal single atoms and sub-nanoclusters by controlling the metal anchoring and migration processes in stages.
[0020] This invention achieves controllable structural adjustment of the catalyst active center from "single-atom dominance" to "coexistence of single atoms and sub-nanoclusters" by precisely controlling the parameters of the segmented sintering process: lowering the first-stage pre-sintering temperature (180–210°C) or extending its time promotes the dispersion and anchoring of the metal precursor, thereby significantly increasing the proportion of single atoms; while increasing the second-stage pyrolysis temperature (600–1000°C) or extending this stage time drives the migration and aggregation of metal atoms, effectively increasing the proportion of sub-nanoclusters. By adjusting the parameter combination of these two stages, the adjacent coexistence structure of transition metal single atoms and sub-nanoclusters can be controlled.
[0021] By comparing the results of the embodiments, the present invention achieves the control of the composite structure of metal single atoms and sub-nano clusters by regulating the anchoring density and dispersion quality of transition metal single atoms in the low-temperature pre-calcination stage and regulating the generation ratio of sub-nano clusters in the high-temperature carbonization stage. The performance data shows that the ratio of single atoms to sub-nano clusters needs to be in the optimized range to obtain the best performance: too many single atoms (as in Example 7) will lead to an imbalance in the reaction steps; too many clusters (as in Example 6) will reduce the atomic utilization and intrinsic activity; while when the two are made atomically proximate and electronically synergistic through process control (as in Examples 1 and 8), the catalyst can exhibit high activity and excellent kinetics in the hydrogen evolution reaction. Attached Figure Description
[0022] Figure 1 A scanning electron microscope image of the Co-NC-1 catalyst prepared in Example 1; Figure 2 Electron micrographs of some embodiments and comparative examples; Figure 2 a is an aberration-corrected high-angle annular dark-field scanning transmission electron microscope image of the CoSAs / NC catalyst prepared in Comparative Example 1. Figure 2 b is a scanning electron microscope image of the Co-NC-1 catalyst prepared in Example 1. Figure 2 c is an aberration-corrected high-angle annular dark-field scanning transmission electron microscope image of the Co-NC-1 catalyst prepared in Example 1. Figure 2 d is a scanning electron microscope image of the Co-NC-2 catalyst prepared in Example 6; Figure 3 LSV curves of Co-NC-1 prepared in Example 1, Co-NC-2 prepared in Example 6, Co-NC-3 prepared in Example 7, Co-NC-4 prepared in Example 8, and CoSAs / NC catalyst prepared in Comparative Example 1 in 1 MKOH; Figure 4 A comparison of LSV curves before and after 5000 CV cycles for the Fe-NC catalyst prepared in Example 2; Figure 5LSV curves of the Fe-NC and FeSAs / NC catalysts prepared in Example 2 in 1 MKOH; Figure 6 The LSV curve of the Ni-NC catalyst prepared in Example 3 in 1 MKOH; Figure 7 The LSV curve of the Cu-NC catalyst prepared in Example 4 in 1 MKOH; Figure 8 LSV curves of the Pt-NC catalyst prepared in Example 5, the PtSAs / NC catalyst prepared in Comparative Example 2, and the PtNPs / NC catalyst prepared in Comparative Example 3 in 0.5 M H₂SO₄; Figure 9 The stability curve of the Pt-NC catalyst prepared in Example 5 in 0.5MH2SO4. Detailed Implementation
[0023] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are only used to illustrate the principles and specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Unless otherwise stated, the experimental methods used in the embodiments are performed according to general standards in the art; the raw materials, reagents, etc. involved, unless otherwise specified, are all conventional products that can be purchased through conventional commercial channels. Any non-substantial modifications and equivalent substitutions made by those skilled in the art based on the technical solutions of the present invention should be considered to fall within the scope defined by the claims of the present invention. Example 1
[0024] Co-NC-1 catalyst with coexistence of Co single atoms and sub-nano clusters 1. Material preparation Dissolve 0.01875 mol zinc nitrate hexahydrate in 100 mL methanol solution, and dissolve 0.1125 mol 2-methylimidazole in 100 mL methanol solution. Mix the two solutions and stir evenly at room temperature to obtain a clear solution A (the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:6).
[0025] 0.00344 mol of cobalt nitrate hexahydrate was dissolved in 20 mL of methanol, denoted as solution B. Solution B was slowly poured into solution A under vigorous stirring, and the mixture was stirred at room temperature for 24 hours. The precipitate was collected by centrifugation, washed thoroughly five times with methanol, and then dried under vacuum at 80°C for 8 hours to obtain Co-Zn / ZIF-8 precursor powder. The powder was then subjected to low-temperature pre-reconstruction at 200°C for 70 min under an argon atmosphere by heating at 5°C / min, followed by a programmed heating to 920°C and holding for 120 min to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.1 M HCl solution for 2 hours to remove unstable metal particles. After washing with deionized water until neutral and drying under vacuum at 80°C, a porous carbon-supported metal single-atom-metal sub-nano cluster synergistic catalyst, i.e., a Co single-atom-sub-nano cluster synergistic catalyst with a metal loading of 1.5 wt%, denoted as Co-NC-1, was obtained. Scanning electron microscope (SEM) images ( Figure 1 The results showed that the obtained Co-NC-1 catalyst maintained a regular octahedral morphology, indicating that the porous carbon support of the prepared catalyst was an octahedral porous carbon prepared with a zinc-based zeolite imidazole framework as the precursor. Further characterization using aberration-corrected high-angle annular dark-field scanning transmission electron microscopy clearly revealed the simultaneous presence of atomically dispersed Co bright spots (single atoms) and sub-nano clusters formed by the aggregation of several atoms in the catalyst. Figure 2 c). More importantly, as can be seen in the figure, single atoms and sub-nanometer clusters are spatially adjacent on the carbon support, forming a typical "dual-active-site" synergistic structure.
[0026] 2. Performance Evaluation The hydrogen evolution reaction occurs in 1 M KOH solution at 10 mA cm⁻¹. -2 The overpotential at current density is 48mV ( Figure 3 The Tafel slope is 50mVdec. -1 During a 50-hour constant voltage electrolysis test, the current density decayed by less than 5%, demonstrating its great potential as a highly efficient and stable hydrogen evolution catalyst. Example 2
[0027] Fe-NC catalysts where Fe single atoms and sub-nano clusters coexist 1. Material preparation 0.01875 g of zinc nitrate hexahydrate was dissolved in 100 mL of methanol solution, and 0.0750 mol of 2-methylimidazole was dissolved in 100 mL of methanol solution. The two solutions were mixed and stirred evenly at room temperature to obtain a clear solution A (molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4). 0.00248 mol of ferric nitrate nonahydrate was dissolved in 20 mL of methanol, denoted as solution B. Solution B was slowly poured into solution A under vigorous stirring, and stirred at room temperature for 24 hours. The precipitate was collected by centrifugation, washed thoroughly with methanol five times, and then dried under vacuum at 80°C for 10 hours to obtain Fe-Zn / ZIF-8 precursor powder. The powder was subjected to low-temperature pre-reconstruction at 200°C for 60 min under an argon atmosphere by heating at 5°C / min, and then heated to 950°C at the same rate and held for 120 min to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.05M HCl solution for 2 hours to remove unstable metal particles. After washing with deionized water until neutral and vacuum drying at 80°C, a Fe single-atom-sub-nano cluster synergistic catalyst with a final metal loading of 1.2wt% was obtained, denoted as Fe-NC.
[0028] 2. Performance Evaluation The electrocatalytic hydrogen evolution performance of this Fe-NC catalyst was evaluated using a three-electrode system in a 1.0 MkOH electrolyte. The catalyst achieved an efficiency of 10 mA / cm². -2 The overpotential required for current density is as low as 47mV ( Figure 5 The Tafel slope is 49mVdec. -1 After passing 5000 cycles of cyclic stability testing, its overpotential shifted negatively by only about 5mV. Figure 4 This indicates that the catalyst has excellent structural stability, which is attributed to the synergistic stabilizing effect of the coexistence of single atoms and sub-nano clusters. Example 3
[0029] Ni-NC catalysts where Ni single atoms and sub-nano clusters coexist 1. Material preparation 0.01875 mol of zinc nitrate hexahydrate and 0.0375 mol of 2-methylimidazole were dissolved in 100 mL of methanol. The two solutions were mixed and stirred at room temperature to obtain a clear solution A (molar ratio of zinc nitrate hexahydrate to 2-methylimidazole: 1:2). 0.00172 mol of nickel nitrate hexahydrate was dissolved in 20 mL of methanol, denoted as solution B. Solution B was slowly poured into solution A under vigorous stirring, and the mixture was stirred at room temperature for 24 hours. The precipitate was collected by centrifugation, washed thoroughly five times with methanol, and then dried under vacuum at 60°C for 10 hours to obtain Ni-Zn / ZIF-8 precursor powder. The powder was subjected to low-temperature pre-reconstruction at 150°C for 120 min at a rate of 2°C / min under an argon atmosphere, followed by a programmed temperature increase to 600°C and holding at the same rate for 60 min to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.01M HCl solution for 5 hours to remove unstable metal particles. After washing with deionized water until neutral and vacuum drying at 80°C, a Ni single-atom-sub-nano cluster synergistic catalyst with a final metal loading of 0.5wt% was obtained, denoted as Ni-NC.
[0030] 2. Performance Evaluation The Ni-NC catalyst underwent systematic electrochemical testing. In a 0.5 M H₂SO₄ electrolyte, it exhibited excellent HER performance, reaching 10 mA / cm⁻¹. -2 The overpotential required for the current density is only 68mV ( Figure 6 The Tafel slope is 53mVdec. -1 . Example 4
[0031] Cu-NC catalysts where Cu single atoms and sub-nano clusters coexist 1. Material preparation 0.01875 mol of zinc nitrate hexahydrate and 0.0750 mol of 2-methylimidazole were dissolved in 100 mL of methanol. The two solutions were mixed and stirred at room temperature to obtain a clear solution A (molar ratio of zinc nitrate hexahydrate to 2-methylimidazole: 1:4). 0.00828 mol of copper nitrate trihydrate was dissolved in 20 mL of methanol, denoted as solution B. Solution B was slowly poured into solution A under vigorous stirring, and the mixture was stirred at room temperature for 24 hours. The precipitate was collected by centrifugation, washed thoroughly five times with methanol, and then dried under vacuum at 100°C for 4 hours to obtain Cu-Zn / ZIF-8 precursor powder. The powder was subjected to low-temperature pre-reconstruction at 250°C for 40 min under an argon atmosphere by heating at 5°C / min, followed by a programmed temperature increase to 750°C and holding at the same rate for 150 min to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.05M HCl solution for 3 hours to remove unstable metal particles. After washing with deionized water until neutral and vacuum drying at 100°C, a Cu single-atom-sub-nano cluster synergistic catalyst with a final metal loading of 1.9wt% was obtained, denoted as Cu-NC.
[0032] 2. Performance Evaluation This high-Cu supported catalyst exhibits good HER activity. In 1.0 MkOH, its HER performance reaches 10 mA / cm². -2 The required overpotential for the current density is 51mV. Figure 7 After 5000 CV cycles, the overpotential decayed by only 6mV, demonstrating excellent stability. Example 5
[0033] Pt-NC catalysts where Pt single atoms and sub-nano clusters coexist 1. Material preparation 0.01875 mol of zinc nitrate hexahydrate and 0.0937 mol of 2-methylimidazole were dissolved in 100 mL of methanol. The two solutions were mixed and stirred at room temperature to obtain a clear solution A (molar ratio of zinc nitrate hexahydrate to 2-methylimidazole: 1:5). 0.00488 mol of chloroplatinic acid was dissolved in 20 mL of methanol, denoted as solution B. Solution B was slowly poured into solution A under vigorous stirring, and the mixture was stirred at room temperature for 24 hours. The precipitate was collected by centrifugation, washed thoroughly five times with methanol, and then dried under vacuum at 80°C for 8 hours to obtain Pt-Zn / ZIF-8 precursor powder. The powder was subjected to low-temperature pre-reconstruction at 210°C for 60 min under an argon atmosphere by heating at 5°C / min, followed by a programmed temperature increase to 1000°C and holding at the same rate for 120 min to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.05M HCl solution for 2 hours to remove unstable metal particles. After washing with deionized water until neutral and vacuum drying at 80°C, a Pt single-atom-sub-nano cluster synergistic catalyst, denoted as Pt-NC, was obtained. Inductively coupled plasma atomic emission spectrometry results showed that the Pt loading in the catalyst was 5 wt%.
[0034] 2. Performance Evaluation In 0.5MH2SO4, its HER performance is excellent, reaching 10 mAcm. -2 The required overpotential for the current density is 10mV. Figure 8 The Tafel slope is 45mVdec. -1 And at 50mAcm -2 The activity decay is negligible after 100 hours of operation at the current density. Figure 9 ). Example 6
[0035] Co-NC-2 catalyst with coexistence of Co single atoms and sub-nano clusters The same preparation steps and synthesis conditions as in Example 1 were used, except that the carbonization temperature was increased to 980°C and the time was extended to 150 min; the remaining preconditioning, acid washing, and drying steps were the same. The final synergistic catalyst was named Co-NC-2. (Compared to Example 1) Figure 2 Comparing the microstructure of b), it can be seen that, under the same scale, no obvious isolated metal particles are visible in this catalyst. Figure 2 (d) This indicates that increasing the pyrolysis temperature and extending the holding time significantly promoted the migration and aggregation of metal atoms, resulting in a significant increase in the proportion of sub-nano clusters and a corresponding decrease in single-atom dispersion sites. This structural change directly affected its catalytic performance: in 1M KOH electrolyte, Co-NC-2 at 10 mA cm⁻¹... -2 The hydrogen evolution overpotential rises to 61 mV at current density. Figure 3 The Tafel slope is 54mVdec. -1 These results indicate that excessive metal aggregation reduces the atomic utilization efficiency of active sites and weakens the synergistic catalytic effect between single atoms and clusters. Example 7
[0036] Co-NC-3 catalyst with coexistence of Co single atoms and sub-nano clusters The same preparation steps and synthesis conditions as in Example 1 were used, except that the temperature of the pre-conditioning step was changed to 230°C and the time to 90 min, while the remaining carbonization, acid washing, and drying steps remained the same. The final synergistic catalyst was named Co-NC-3. Compared to Example 1, extending the pre-conditioning temperature and time promoted more complete dispersion and anchoring of the metal precursor, making the subsequent carbonization stage more challenging for sub-nanoclusters and increasing the relative proportion of single-atom sites. Hydrogen evolution tests were performed in 1 M KOH at 10 mA cm⁻¹. -2 The overpotential at current density is 70mV. Figure 3 The Tafel slope is 57mVdec. -1 . Example 8
[0037] Co-NC-4 catalyst with coexistence of Co single atoms and sub-nano clusters The same preparation steps and synthesis conditions as in Example 1 were used, except that the temperature of the preconditioning step was changed to 200°C and the time to 100 min, while the remaining carbonization, acid washing, and drying steps remained the same. The final synergistic catalyst was named Co-NC-4. Compared to Example 1, the preconditioning time was extended by 30 min, which strengthened the anchoring of the metal precursor, increased the difficulty of single-atom migration during subsequent carbonization, and improved the relative proportion of single-atom sites. Hydrogen evolution tests were performed at 1 MKO, with a hydrogen evolution overpotential of 52 mV and a Tafel slope of 51 mVdec. -1 The performance was comparable to that of Example 1, indicating that adjusting the pre-conditioning time affects the structural composition of the catalyst. By synergistically controlling the pre-calcination dispersion and carbonization reconstruction, a synergistic catalytic structure with excellent performance can be obtained.
[0038] Comparative Example 1 Co single-atom catalyst The amount of cobalt nitrate hexahydrate added in Example 1 was adjusted to 0.000687 mol to prepare Co-Zn / ZIF-8 precursor powder. It was placed in an argon atmosphere and heated directly to 920 °C at a rate of 5 °C / min and held for 120 minutes to complete the carbonization and nitrogen doping process. The pyrolysis product was acid-washed with 0.1 M HCl solution for 2 hours to remove unstable metal species, then repeatedly washed with deionized water until neutral, and vacuum dried at 80 °C to obtain a pure cobalt single-atom catalyst, denoted as CoSAs / NC. Aberration-corrected high-angle annular dark-field scanning electron microscopy characterization showed that the cobalt species in the synthesized CoSAs / NC catalyst were atomically dispersed. Compared with Example 1, the cobalt atoms were more uniformly dispersed, and no obvious cluster structure was observed. Hydrogen evolution reaction tests were conducted in 0.5 M H₂SO₄ electrolyte. The catalyst showed a hydrogen evolution reaction at 10 mA cm⁻¹. -2 The overpotential at the current density is 110 mV, and the Tafel slope is 91 mVdec. -1 Its catalytic activity is significantly lower than that of the cobalt single-atom and sub-nano cluster synergistic catalyst system prepared in this invention, which reflects the limitations of a single-atom structure in terms of reaction kinetics and overall catalytic activity.
[0039] Comparative Example 2 Pt single-atom catalyst The amount of chloroplatinic acid added in Example 5 was changed to 0.000965 mol to obtain Pt-Zn / ZIF-8 precursor powder. This powder was heated to 1000°C at a heating rate of 5°C / min and held for 120 min under an argon atmosphere to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.05M HCl solution for 2 hours, washed with deionized water until neutral, and vacuum-dried at 80°C to obtain a Pt single-atom catalyst, denoted as PtSAs / NC. In 0.5M H₂SO₄, its HER performance was between that of the Pt-NC catalyst and PtNPs / NC, reaching 10 mA / cm⁻¹. -2 The required overpotential for the current density is 32mV. Figure 8 The Tafel slope is 30mVdec. -1 .
[0040] Comparative Example 3 Pt nanoparticle catalyst The Pt-Zn / ZIF-8 precursor powder obtained in Example 5 was heated to 1000°C at a heating rate of 5°C / min and held for 120 min under an argon atmosphere to complete the carbonization and nitrogen doping process. Finally, the pyrolysis product was acid-washed with 0.05M HCl solution for 2 hours to remove unstable metal particles. After washing with deionized water until neutral and vacuum drying at 80°C, Pt nanoparticle catalyst, denoted as PtNPs / NC, was obtained. In 0.5M H₂SO₄, its HER performance was worse than that of the Pt-NC catalyst, reaching 10 mA / cm⁻¹. -2 The required overpotential for the current density is 40mV. Figure 8 The Tafel slope is 36mVdec. -1 .
[0041] Table 1 Performance Comparison Table As can be seen from the table above, by comparing the results of the examples, the present invention achieves the control of the composite structure of metal single atoms and sub-nano clusters by regulating the anchoring density and dispersion quality of transition metal single atoms in the low-temperature pre-calcination stage and regulating the generation ratio of sub-nano clusters in the high-temperature carbonization stage. The performance data shows that the ratio of single atoms to sub-nano clusters needs to be in the optimized range to obtain the best performance: too many single atoms (as in Example 7) will lead to an imbalance in the reaction steps; too many clusters (as in Example 6) will reduce the atomic utilization rate and intrinsic activity; while when the two are controlled by process to achieve atomic proximity and electronic synergy (as in Examples 1 and 8), the catalyst can exhibit high activity and excellent kinetics in the hydrogen evolution reaction.
Claims
1. A method for preparing a porous carbon-supported metal single-atom-metal sub-nano cluster synergistic catalyst, characterized in that, Includes the following steps: (1) Mix a methanol solution containing zinc nitrate hexahydrate with a methanol solution containing 2-methylimidazole until homogeneous to obtain solution A; (2) Dissolve the transition metal salt in methanol and stir until homogeneous to obtain solution B; (3) Add solution B to solution A and stir to react; centrifuge, wash and vacuum dry to obtain M-Zn / ZIF-8 precursor; (4) Under an inert atmosphere, the M-Zn / ZIF-8 precursor was subjected to segmented sintering, acid washing, centrifugation, washing and vacuum drying to obtain a porous carbon-supported metal single atom-metal sub-nano cluster synergistic catalyst. The segmented sintering refers to first heating the temperature to 150-250℃ at a heating rate of 2-5℃ / min and holding it at that temperature for 40-120min; then heating the temperature to 600-1000℃ at a heating rate of 2-5℃ / min and holding it at that temperature for 60-150min. The porous carbon support has a dual-active-site structure of transition metal single atoms and sub-nano clusters on its surface; the metal loading in the porous carbon-supported metal single-atom-metal sub-nano cluster synergistic catalyst is 0.5–5 wt%. The porous carbon support is an octahedral porous carbon prepared using a zinc-based zeolite imidazole framework as a precursor, and the transition metal is one of Fe, Co, Ni, Cu, and Pt; the transition metal single atoms and sub-nano clusters are distributed in close proximity at the atomic scale, forming a synergistic catalytic active center.
2. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2 to 6.
3. The preparation method according to claim 1, characterized in that, In step (3), the vacuum drying temperature is 60-100℃ and the vacuum drying time is 4-10h.
4. The preparation method according to claim 1, characterized in that, In step (4), the pickling solution is 0.01-0.1M dilute hydrochloric acid, the pickling time is 0.5-5h, the vacuum drying temperature is 60-100℃, the vacuum drying time is 4-10h, the inert atmosphere is nitrogen or argon, and the flow rate is 50-200mL / min.
5. The preparation method according to claim 1, characterized in that, The segmented sintering refers to first heating the temperature to 150-250℃ at a heating rate of 2-5℃ / min and holding it at that temperature for 40-120min; then heating the temperature to 750-950℃ at a heating rate of 2-5℃ / min and holding it at that temperature for 60-150min.
6. The application of a porous carbon-supported metal single-atom-metal sub-nano cluster synergistic catalyst prepared by any one of claims 1 to 5 in the electrocatalytic hydrogen evolution reaction.
Citation Information
Patent Citations
Preparation method of high-dispersion amorphous ruthenium-based catalyst and application of high-dispersion amorphous ruthenium-based catalyst in catalyzing selective hydrogenation of benzene to prepare cyclohexene
CN115888783A
